Analisis Kebangkrutan Menggunakan Metode Altman Z-Score, Zmijewski, dan Grover Pada PT. Vale Indonesia Tbk - Fitra Ramadhan,; Aulya Rahmadani,; Ridha Arsyika, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2022)
This research is motivated by the desire to provide an overview of the method of bankruptcy, in terms of bankruptcy analysis. This article aims to provide a comprehensive description and description of bankruptcy analysis methods which are classified into several methods, including: Altman Z-Score, Zmijewski, and Grover methods. The research method used is descriptive with a quantitative approach. The place in this research is PT. Vale Indonesia Tbk period 2015-2020. This study uses secondary data in the form of financial statements obtained from the financial statements of PT. Vale Indonesia Tbk for the 2015-2020 period which was taken through the website www.idx.co.id. The results of the study using the Altman Z-Score, Zmijewski, and Grover methods showed that PT. Vale Indonesia is in a safe zone (financially healthy) and far from financial distress, it is possible that the company will continue to grow upwards and become the mecca of HIMBARA in the future.